DETERMINAN YANG MEMPENGARUHI KEPUTUSAN INVESTASI OLEH INVESTOR - Nurasik; Sarwenda Biduri; Santi Rahma Dewi; Mukhammad Amar Musliq (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to determine the effect of profitability, liquidity, leverage and stock prices on investment decisions by investors (study of food and beverage companies listed on the Indonesian Stock Exchange in 2016-2019). The sampling method used is purposive sampling method. The number of companies sampled in this study were 13 Food and Beverages Listed on the IDX for the 2016-2019 period. The data used is secondary data. The data analysis method used in this study is Multiple Linear Regression. The results of this study indicate that Profitability has an effect on Investment Decisions. Liquidity has an effect on investment decisions. Leverage has an effect on Investment Decisions. Stock Prices have an effect on Investment Decisions.